Degradation of lithium-ion batteries in electric vehicles - Rauker, Josip; Šaban, Andrija (Crisis Management Days, 2025)
Abstract: The sale of electric vehicles is increasing year by year. Consequently, the number of used electric vehicles entering the market is also growing. Most manufacturers provide a warranty ensuring that the battery capacity will not drop below 70% after eight years. Since electric vehicles are relatively new and there are not many used electric vehicles older than eight years, many buyers are skeptical about them due to potentially high battery replacement costs. The degradation mechanisms of lithium-ion batteries are well understood today. The aim of this paper is to present the most significant degradation mechanisms of lithium-ion batteries and their impact on battery capacity loss, depending on battery age and the number of charging cycles. (Birkl, i dr. 2017) (Keil i Jossen 2017) (Laxman, i dr. 2023) (Sarasketa-Zabala, i dr. 2015). 1. INTRODUCTION Today, there are more and more electric cars on the roads. With the increase in sales of new electric vehicles, the number of electric vehicles in the used car market is also growing. Buyers of used vehicles generally have little experience with used electric cars and tend to avoid them due to fears of high battery replacement costs after the warranty expires. There are two main criteria when choosing a used vehicle with an internal combustion engine: the age of the vehicle and the mileage. While there is no clear consensus on which is more important, most used car buyers prefer a vehicle with lower mileage, as this means the engine, potentially most expensive part to replace, has undergone fewer operating hours. For electric vehicles, lower mileage means fewer charging cycles, which should have a positive impact on battery capacity. Battery capacity decreases as the number of charging cycles increases. Battery manufacturers typically guarantee that a battery can withstand a certain number of charging cycles, but battery longevity also depends on many other factors. 2. METHODOLOGY This paper was written using information from available literature. Works by authors who conducted tests on various types of lithium-ion batteries were used. The described tests aimed to study the fundamental degradation mechanisms of lithium-ion batteries, their impact on capacity and power loss, and potential methods for accurately diagnosing battery condition. 3. RESULTS Degradation of batteries in electric vehicles is a complex phenomenon influenced by many factors. Battery degradation manifests as capacity loss and power loss. The primary causes of battery degradation include time (battery aging), temperature, charging rate, state of charge, and mechanical stress. The Battery Management System (BMS) is the key system that can impact battery longevity. By understanding the causes of degradation and monitoring them throughout the battery's lifespan, battery management systems can be improved to extend battery life. Additionally, algorithms have been developed to estimate battery lifespan, aiming to predict capacity loss and the remaining number of cycles for a used battery.